Life, a non-negotiable good - Dip, Ricardo (Derecho Público Iberoamericano, 2020)
The paper argues that the thesis about the sanctity of human life can only be justified in a criteria that transcends the constructivist voluntarism and nihilist approaches, an ideological element that bounds an important part of the contemporary human rights theory. That voluntarism is capable of turn the most valuable legally protected goods into negotiable things, and has the capacity to influence the statutory legislation and the case-law even in countries with deep Christian roots, such as Brazil.